The impact of organizing international sports events: a case study of three Portuguese sports federations international sports events: strategic drivers and outcomes - Barreto, Tomás Sousa Faro e Silva (2021)
This work project aims to assess the capacity of international sports events to impact sports participation and sports development in Portugal, generate financial resources for sports federations, and provide positive outcomes for local communities. For this purpose, three Portuguese sports federations were investigated, through semi-structured interviewees with key stakeholders, collection of event documents and reports, and the analysis of relevant sports data and statistics. Consequently, despite their limited effect on attracting new practitioners and adding financial value, international sports events establish conditions for sports excellence and foster synergetic relationships between sports federations and host communities.